Evaluation of Undergraduate Orthodontic Courses at the Faculty of Dentistry in King Abdulaziz University - Fahad F. Alsulaimani (Journal of King Abdulaziz University: Medical Sciences, 2023)
The undergraduate orthodontic courses at the Faculty of Dentistry, King Abdulaziz University are two and a half academic year, starting from the 4th year with an introduction to orthodontics. During the 5th year, students get exposed to different treatment modalities. During the 6th and final year, students are exposed to clinical cases. The aim of this study was to evaluate the content of these courses, teaching techniques, and the importance of teaching orthodontics to the undergraduate students. Nineteen questions were distributed to the graduating class of 2011-12 (40 male and 55 females). The topics covered were: 1) the importance of orthodontic teaching to the undergraduate students, 2) the importance of the laboratory projects, 3) the teaching methods, and 4) the competency of the student after finishing the orthodontic courses. Answers were analyzed according to gender and final grades. Pearson’s chi-squared test was used to evaluate significance. There was no significant difference between male and female in all of the 19 questions. When analyzing the data according to the final grades, there were also no significant differences in most of the questions. Most of the graduating students were satisfied with the content of the orthodontic courses.